2022
DOI: 10.1002/ajmg.a.62759
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study of obstructive heart defects among participants in the National Birth Defects Prevention Study

Abstract: Obstructive heart defects (OHDs) share common structural lesions in arteries and cardiac valves, accounting for ~25% of all congenital heart defects. OHDs are highly heritable, resulting from interplay among maternal exposures, genetic susceptibilities, and epigenetic phenomena. A genome-wide association study was conducted in National Birth Defects Prevention Study participants (N discovery = 3978; N replication = 2507), investigating the genetic architecture of OHDs using transmission/disequilibrium tests (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Information regarding maternal exposures and lifestyle factors hypothesized to impact organogenesis were obtained through structured computer‐assisted maternal interviews conducted by research staff. Once a woman completed the interview, DNA samples of her child, the biological father, and herself were collected (Rashkin et al, 2022). Funding for a genome wide association study was awarded to CAH, PI, from the Eunice Kennedy Shriver National Institute of Child Health and Human Development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding maternal exposures and lifestyle factors hypothesized to impact organogenesis were obtained through structured computer‐assisted maternal interviews conducted by research staff. Once a woman completed the interview, DNA samples of her child, the biological father, and herself were collected (Rashkin et al, 2022). Funding for a genome wide association study was awarded to CAH, PI, from the Eunice Kennedy Shriver National Institute of Child Health and Human Development.…”
Section: Methodsmentioning
confidence: 99%
“…Samples from five NBDPS sites (Arkansas, California, Georgia, Iowa, and Texas) were included as the Phase I sample of the GWAS, and samples from the other four NBDPS sites (Massachusetts, New York, North Carolina, and Utah) were included as the Phase II sample. Details of the sample collection and quality controls can be found elsewhere (Rashkin et al, 2022).…”
Section: Application To Chd Gwas Datamentioning
confidence: 99%
“…There is also evidence, albeit incomplete, that common genetic variants contribute to left sided congenital heart defects [ 47 , 48 , 49 , 50 , 51 ]. Genome wide association studies have found loci that meet standard statistical criteria for significance, but the loci identified have not yet overlapped or been strongly validated.…”
Section: Complex Inheritancementioning
confidence: 99%